DETERMINANTS OF CLOUD-BASED ACCOUNTING ADOPTION: INSIGHTS FROM ACCOUNTING PROFESSIONALS IN SRI LANKA - Bandara, K.G.Dhammika B. Katupulla; B.A.N.Krishantha; C.G.Kothalawala (ZILLZELL MEDIA PRIMA, 2025)
Cloud-based accounting adoption among accounting professionals in Sri Lanka is influenced by various factors, as explored in this study. With the evolution of technology in the accounting profession, cloud accounting offers significant advantages, including cost savings, scalability, and real-time access to financial data. This research, based on a sample of 100 accounting professionals, employed multiple regression analysis to examine the impact of these determinants on cloud-based accounting adoption. The findings reveal that factors such as IT capability, compatibility, perceived value, relative advantage, top management support, and competitive pressure significantly drive cloud-based accounting adoption in Sri Lanka. Conversely, factors like the innovativeness of senior executives, IT infrastructure, and perceived cost do not show significant effects. These results underscore the importance of aligning technology with organizational needs, highlighting the need for user-friendly interfaces, comprehensive training, and effective marketing strategies to promote adoption. Based on these findings, recommendations are provided to encourage cloud-based accounting adoption, including enhancing compatibility, mitigating complexity, promoting perceived value and relative advantage, leveraging top management support, and capitalizing on competitive pressure.